Multi-Input Power Converter for Renewable Energy Sources using Active Current Sharing Schemes - Mazelan, F.N. (Institute of Electrical and Electronics Engineers Inc., 2019)
In this paper, a multi-input power converter (MIPC) dedicated for renewable energy system (RES) using an active current sharing scheme is proposed. The designed power converter consists of three inputs from RES which are photovoltaic and fuel cells. It is known that the RES has a varying and intermittent characteristic in its output. Hence, the control scheme is required to stabilize the regulated output. This paper mainly focuses on designing an MIPC which employs an averaged current sharing mode as its active current sharing error signalling processing control strategy. A conventional control for the same MIPC converter using pulse width generator were also simulated for comparison purposes. The MIPC with three varying input voltage was design to produce 400 V DC. The simulation of both MIPC under different input voltage condition was carried out. The results show that the proposed scheme was able to regulate and provide the desired output voltage to a certain input voltage variation as opposed to the fixed control. Â© 2019 IEEE.